A high specific surface area porous carbon skeleton derived from MOF for high-performance Lithium-ion capacitors. Issue 1 (September 2021) - Chen, Cheng; Li, Xinran; Li, Junxiang; Li, Pengyu; Wu, Mengqiang
Abstract: Lithium-ion capacitor (LICs) is expected to replace the traditional double-layer capacitor and lithium-ion battery as a new energy storage device. However, the slow de/intercalation of Li + in battery-type electrodes (anode) limits the power density of lithium-ion capacitors (LICs). In this work, a high specific surface area porous carbon skeleton (Z-T-PC) is synthesized derived from MOF (Zn-TFBDC). Benefit from the large specific surface area and 3D conductive skeleton, the Z-T-PC shows that the sample has a high specific capacity and stable cycling performance as the LIC anode. The assembled asymmetric LICs exhibit high power density and energy density with Z-T-PC anode. The work provides new thinking for the application of the novel anode material of LICs.